Latkes and applesauce : a Hanukkah story - Manushkin, Fran; Spowart, Robin (New York : Scholastic Inc., 1992)
When a blizzard leaves a family housebound one Hanukkah, they share what little food they have with some starving animals who later return the favor
When a blizzard leaves a family housebound one Hanukkah, they share what little food they have with some starving animals who later return the favor
Reprint. Originally published: 1990.
Includes bibliographical references.
Keywords: Hanukkah -- Fiction; Hanukkah -- Fiction